2012
DOI: 10.1111/j.1365-2435.2012.01974.x
|View full text |Cite
|
Sign up to set email alerts
|

Widespread intraspecific organismal stoichiometry among populations of the Trinidadian guppy

Abstract: Summary1. Ecological stoichiometry expresses ecological interactions as the balance between multiple elements. It relates the ecological function of organisms to their elemental composition, or their organismal stoichiometry. Organismal stoichiometry is thought to reflect elemental investments in life history and morphology acting in concert with variability in abiotic or environmental conditions, but the relative contribution of these factors to natural variability in organismal stoichiometry is poorly unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
102
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(111 citation statements)
references
References 58 publications
6
102
0
1
Order By: Relevance
“…We were surprised that river explained only a small portion of variation in salmon %P because spatial differences in %P have been found in other fishes (Boros et al 2012, El-Sabaawi et al 2012. El-Sabaawi and colleagues (2012) found that the presence of limestone in watersheds had a greater influence on %P of Trinidadian guppies than did genetic lineage because limestone deposits have direct effects on the amount of P cycling in aquatic ecosystems and thus a different biogeochemical setting for juvenile growth.…”
Section: Whole Body % Phosphorusmentioning
confidence: 99%
See 2 more Smart Citations
“…We were surprised that river explained only a small portion of variation in salmon %P because spatial differences in %P have been found in other fishes (Boros et al 2012, El-Sabaawi et al 2012. El-Sabaawi and colleagues (2012) found that the presence of limestone in watersheds had a greater influence on %P of Trinidadian guppies than did genetic lineage because limestone deposits have direct effects on the amount of P cycling in aquatic ecosystems and thus a different biogeochemical setting for juvenile growth.…”
Section: Whole Body % Phosphorusmentioning
confidence: 99%
“…However, work on other fishes has documented significant intraspecific variation in %P arising from sex, ontogeny, size, physical habitat, feeding history, and geographic location (Hendrixson et al 2007, McIntyre and Flecker 2010, El-Sabaawi et al 2012. The magnitude of variation in %P within salmonid species in the wild is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both field surveys were conducted during the dry seasons in 2010 and 2011, respectively, and took place in mountain streams in the Northern Range of Trinidad, West Indies (Supplementary Table 1). The 2010 field survey was carried out to assess gut bacterial diversity across streams and guppy populations; from 20 April through 2 May 2010, 40 Trinidadian guppies were collected from previously categorized HP and LP habitats El-Sabaawi et al, 2012) that tend to differ in a number of ecosystem characteristics, including canopy coverage and primary productivity (Grether et al, 2001). …”
Section: Field Collectionsmentioning
confidence: 99%
“…This ability of a heterotrophic organism to maintain its body elemental composition relatively constant, despite varying diets, is defined as homeostasis (Sterner and Elser, 2002). However, some studies have pointed out that in animal species organismal stoichiom etry may not be as constant as previously thought, so that consumers may not be strictly homeostatic (Hendrixson et al, 2007;Boros et al, 2012Boros et al, , 2015El-Sabaawi et al, 2012a;El-Sabaawi et al, 2012b;Benstead et al, 2014).…”
Section: Introductionmentioning
confidence: 98%